The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1002/pros.20387
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screening of the androgen receptor promoter and untranslated regions in prostate cancer

Abstract: Recurrent mutations in the promoter or UTRs of AR seem to be rare, and thus not likely mechanisms for the increased expression of the gene in the androgen ablation-resistant prostate cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Although no functional analysis was described, it is interesting that the C214A change could disrupt a potential, but functionally unconfirmed, Sp1 binding site (see Wang and Ferrari 2006). However, a later study examining tumour and normal prostate tissue, together with five prostate cancer cell lines and xenograft samples, concluded that mutations were only present in cultured cell lines (DU145 and LAPC4) and a small number of xenografts (Waltering et al 2006). There was no evidence of recurrent mutations in the promoter, 5' and 3 UTRs in patient samples.…”
Section: Clinical Mutations In the 5'utrmentioning
confidence: 96%
“…Although no functional analysis was described, it is interesting that the C214A change could disrupt a potential, but functionally unconfirmed, Sp1 binding site (see Wang and Ferrari 2006). However, a later study examining tumour and normal prostate tissue, together with five prostate cancer cell lines and xenograft samples, concluded that mutations were only present in cultured cell lines (DU145 and LAPC4) and a small number of xenografts (Waltering et al 2006). There was no evidence of recurrent mutations in the promoter, 5' and 3 UTRs in patient samples.…”
Section: Clinical Mutations In the 5'utrmentioning
confidence: 96%
“…In addition, 44 unselected, genome Phi-amplified (GenomiPhi Amplification kit, Amersham, GE Healthcare, UK), prostate tumour samples from the Tampere region (Waltering et al, 2006) were analysed. Of these, 28 were previously untreated cancers (primary), 12 were hormone-refractory, and four were characterised as benign prostate hyperplasia.…”
Section: Sample Materialsmentioning
confidence: 99%
“…5,6 Two important mechanisms underlying the development and progression of CRPC, which can be exploited therapeutically, are the overexpression of IL-6 and hypersensitivity or mutation of the androgen receptor, both of which contribute to CRPC. [22][23][24][25][26] Unfortunately, the current DTX regimen does not have a role in these mechanisms. It has been demonstrated that bicalutamide (BCL) can effectively block the effect of IL-6 on a mutated androgen receptor, resulting in the apoptosis of prostate cancer cell lines (DU-145 and LNCAP) in vitro.…”
Section: Introductionmentioning
confidence: 99%